ChemInform Abstract: Electrochemical Performance of Nanocrystalline Li2CoTiO4 Cathode Materials for Lithium ion Batteries. Issue 52 (29th December 2014) - Yang, Meng; Zhao, Xiangyu; Ma, Liqun; Yang, Hui; Shen, Xiaodong; Bian, Yajuan
Abstract The title cathode materials with different nanostructures are synthesized by a sol—gel method from stoichiometric amounts of Li(OAc), Co(OAc)2, and Ti(O‐Bu)4 dispersed in EtOH (80 °C, 20 h) and subsequent heat treatment at 550, 600, 650, and 700 °C for 10 h under nitrogen flow.